Synthesized copper oxide nanoparticles via the green route act as antagonists to pathogenic root-knot nematode, Meloidogyne incognita - Amir Khan; Manar Fawzi Bani Mfarrej; Mohtaram Danish; Mohammad Shariq; Mohd. Farhan Khan; Moh Sajid Ansari; Mohamed Hashem; Saad Alamri; Faheem Ahmad (Green Chemistry Letters and Reviews, 2022)
This investigation explains the green synthesis, characterization and biocontrol potential of copper oxide nanoparticles (CuONPs) against second-stage juveniles (J2s) of root-knot nematode, Meloidogyne incognita infesting chickpea. Mono-disperse, spherical, pure CuONPs were synthesized from Jatropha curcas leaf with particle sizes ranging from 5 to 15 nm in diameter. Antagonistic activities of synthesized CuONPs were studied against Meloidogyne incognita. The highest mortality of J2s was found in the 200 ppm concentration of CuONPs at 24 h of exposure. The exact concentration also showed maximum inhibition of J2s hatching from egg masses after six days of exposure. It was worth noting that 25 ppm concentration was the least effective. The pot experiment showed that CuONPs significantly reduced the root infection caused by M. incognita and enhanced chickpea plants’ growth and physiological attributes (Chlorophyll and carotenoid content). The results depicted when the concentration of CuONPs was increased, J2s mortality rate was also increased. We highlighted the antinematode influence of green synthesized CuONPs. Thus, it will offer an excellent eco-friendly strategy to optimize yield under pathogens attack and provide prospects of green synthesized-based nanoparticles development for pests control. Plants mediated CuONPs will also help in resolving the current toxicity concerns and future challenges in the agriculture.